INDUSTRY PROFILE DAN CORPORATE SOCIAL RESPONSIBILITY EXPENDITURE - Ade, Fivetina Wulan; Sudana, I Putu (E-Jurnal Akuntansi, 2017)
Corporate social responsibility expenditure is all expenses incurred in conducting company's social responsibility program. The magnitude of company’s corporate social responsibility expenditure can be influenced by the company's ability to gain  profits and  it’s sensitivity to the environment. This study aimed to examine the effect of profitability on CSR expenditure and the differences of CSR expenditure between high and low profile company's. The study was conducted on companies listed in the Indonesia Stock Exchange in 2012-2015. Sample of 196 observation is obtained with purposive sampling method. Data are analyzed using  stepwise multiple regression.. Statistical test results show that profitability negatively affect on CSR expenditure, while the results of Man-Whitney test shows that there are differences CSR expenditure between high and low profile company's.
Keywords: profitability, CSR expenditure, high profile, low profile